A escola de educação básica e a formação inicial em pedagogia: um estudo de caso - Santos, Tatiana Fruscalso dos (2015)
This study is part of the Training Research Line, Policy and Practice in Education, and it is characterized by being a qualitative research, in order to discuss the importance of the school of Basic Education in the training of teacher trainees. It seeks to interact and understand how happen the teaching practices and curriculum supervised internships in basic education schools. Highlight important points as the trajectory of teacher education in Brazil, the relationship of the School of Basic Education with the University, Teachers in Training, Professors and Teachers Supervisors, whose accounts of experiences contributed to this research. The theoretical contributions anchor up mainly of authors such as Pimenta (2000, 2001 and 2004), Nóvoa (1999, 1995), Morosini (2006, 1992), Arroyo (2000), among others. This work is in an ethnographic case study characterized by the description of the school culture (André 2012). The result shows the importance of training teachers insertion in the school environment and points to a relationship, almost non-existent, between training institutions - school and university - and the desire on the part of the schools studied, that this relationship happen so effective, improving the studies, practices and pedagogical doings of professionals already working in primary education schools and teacher training throughout the course.